E‐cadherin determines Caveolin‐1 tumor suppression or metastasis enhancing function in melanoma cells. (11th April 2013) - Lobos‐González, Lorena; Aguilar, Lorena; Diaz, Jorge; Diaz, Natalia; Urra, Hery; Torres, Vicente A.; Silva, Veronica; Fitzpatrick, Christopher; Lladser, Alvaro; Hoek, Keith S.; Leyton, Lisette; Quest, Andrew F. G.
Summary The role of caveolin‐1 (CAV1) in cancer is highly controversial. CAV1 suppresses genes that favor tumor development, yet also promotes focal adhesion turnover and migration of metastatic cells. How these contrasting observations relate to CAV1 function in vivo is unclear. Our previous studies implicate E‐cadherin in CAV1‐dependent tumor suppression. Here, we use murine melanoma B16F10 cells, with low levels of endogenous CAV1 and E‐cadherin, to unravel how CAV1 affects tumor growth and metastasis and to assess how co‐expression of E‐cadherin modulates CAV1 function in vivo in C57BL/6 mice. We find that overexpression of CAV1 in B16F10 (cav‐1) cells reduces subcutaneous tumor formation, but enhances metastasis relative to control cells. Furthermore, E‐cadherin expression in B16F10 (E‐cad) cells reduces subcutaneous tumor formation and lung metastasis when intravenously injected. Importantly, co‐expression of CAV1 and E‐cadherin in B16F10 (cav‐1/E‐cad) cells abolishes tumor formation, lung metastasis, increased Rac‐1 activity, and cell migration observed with B16F10 (cav‐1) cells. Finally, consistent with the notion that CAV1 participates in switching human melanomas to a more malignant phenotype, elevated levels of CAV1 expression correlated with enhanced migration and Rac‐1 activation in these cells.